TRANSFORMATION OF THE IDEA OF A UNIVERSITY IN MODERN SOCIETY - Оноприенко, В. И. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
New calls of modern world bring in substantial corrective amendments in the idea of university education, keeping humanistic potential of fundamental knowledge and its connection with dominant type of culture.